2015
DOI: 10.1539/joh.14-0111-oa
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence towards Congolese health care workers: A survey of 436 healthcare facilities in Katanga province, Democratic Republic of Congo

Abstract: sity-Objectives: The aim of this study was to investigate workplace violence by patients or their relatives towards health-care workers in Congolese hospitals. Methods: Through the autumn of 2012, a crosssectional survey on workplace violence was conducted in a sample of 2,210 registered health-care workers (989 males and 1,221 females, aged 33 ± 8 years) from 436 hospitals located in the province of Katanga, Democratic Republic of the Congo. Verbal aggression, harassment and physical violence perpetrated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 24 publications
7
38
3
Order By: Relevance
“…The ndings of the present study revealed that 44.6% of nurses were verbally abused. These results are low compared to the studies conducted in different countries, in Malawi (95%) (14), in the South of Ethiopia (90%) (2) in China (65%) (13) in Lebanon (62%) (16), in Gambia (59.8%) (12), in the Democratic Republic of Congo (59.0%) (15) and in Ghana (52.7%) (17).…”
Section: Consequences Of Wpvmentioning
confidence: 58%
See 1 more Smart Citation
“…The ndings of the present study revealed that 44.6% of nurses were verbally abused. These results are low compared to the studies conducted in different countries, in Malawi (95%) (14), in the South of Ethiopia (90%) (2) in China (65%) (13) in Lebanon (62%) (16), in Gambia (59.8%) (12), in the Democratic Republic of Congo (59.0%) (15) and in Ghana (52.7%) (17).…”
Section: Consequences Of Wpvmentioning
confidence: 58%
“…Consequences of WPV the types of WPV, (6.7%) of nurses experienced physical violence. This rate is low compared to the studies conducted in some countries; in North West of Ethiopia (60.2%) (3), in Democratic Republic of Congo (53.6%)(15), in Texas State (USA) (49.8%)(8), in Malawi (22%)…”
mentioning
confidence: 61%
“…This is inconsistent with previous findings, which have found that men are more likely to encounter WPV than are women. [44][45][46] One possible explanation for our finding is the sample size differences between the two genders in this study, that is, there were fewer male than female participants. Some previous studies also did not report on gender; thus, gender differences may shift towards the null or become more pronounced.…”
Section: Discussionmentioning
confidence: 76%
“…Perpetrators may be co-workers, managers, patients or visitors (3). The majority of acts of physical or verbal aggression originate from patients or visitors (4)(5)(6)(7)(8)(9). While most incidents of patient or visitor aggression (PVA) arise in mental health and accident and emergency departments (10,11), PVA also occurs in other clinical settings, such as medical and surgical departments (12,13).…”
Section: Introductionmentioning
confidence: 99%